THE EFFECT OF VARIATIONS IN THE DIAMETER AND NUMBER OF GROUNDSTRAP WINDINGS ON THE PERFORMANCE OF A 150 CC ENGINE - Putra, A.Afriansyah; Paloboran, Marthen; Parenrengi, Syafiuddin; Yusuf, Andi Zufikar; Halim, Muh Bhilal (Jurnal Pendidikan Teknik Mesin, 2024)
This research is a type of experimental research which aims to determine the effect of varying the diameter and number of groundstrap turns on the spark plug cable on power, torque, AFR and fuel consumption of a 150 CC motorbike engine. The results of the research show that there is a significant influence on engine power by using variations in the 0.3 mm diameter of the 260 winding groundstrap with an increase of 0.53 hp. When varying the diameter of 0.6 mm of winding 155 on power there is a significant influence with an increase of 0.52 HP and using a variation of 0.9 mm of winding 103 on power there is a positive influence with an increase of 0.43 HP. The use of groundstrap on engine torque with three types of variations increased by 1.03 Nm, 0.63 Nm and 0.75 Nm. There is no significant effect of using groundstrap on AFR. For the effect of using a groundstrap on fuel consumption, the variations with the most positive influence are the 0.3 mm diameter of the 260 winding and the 0.6 mm diameter of the 155 winding.